PEDIATRIC ANTIPHOSPHOLIPID SYNDROME - Petrovic, Gordana; Pasic, Srdjan (Medicinski podmladak, 2023)
Antiphospholipid syndrome is a multisystemic autoimmune disease characterized by the appearance of arterial and/or venous thrombosis, often in multiple locations, thrombocytopenia and repeated spontaneous abortions in affected pregnant women, due to the permanent presence of antiphospholipid antibodies. It can also occur in children and manifest itself in any period of childhood, from infancy, due to transplacental transfer of maternal antibodies, or de novo production of autoantibodies, to adolescence. Clinical manifestations described in adults can also occur in children but are modified by age characteristics, such as immaturity of the immune or other organ systems, greater exposure to viral and bacterial infections, implementation of routine immunization, absence of thrombogenic risk factors common to adults (hypertension, arteriosclerosis, consumption of cigarettes, alcohol and/or oral contraceptives), as well as the absence of pregnancy. Antiphospholipid antibodies most often used in daily clinical work are anticardiolipin antibodies, anti-β2 glycoprotein I antibodies and lupus anticoagulant. Pathogenic mechanisms have not been investigated in detail, it is assumed that they are similar to the adult form of the disease. However, there is rare evidence of the existence of specific patterns of immune response to individual antigenic components, which may lead to specific production of antiphospholipid antibodies during childhood. It is also important to note that these antibodies can be found in about 25% of healthy children. The Sapporo criteria are used to diagnose antiphospholipid syndrome in adults. They include clinical (vascular thrombosis, repeated fetal losses) and laboratory parameters (persistent presence of one of the antiphospholipid antibodies) in the IgG and/or IgM class, in medium or high titer. The updated Sapporo criteria also apply to children. They include the same laboratory and clinical criteria, except for pregnancy pathology. The differential diagnosis is very broad and requires extensive diagnostics. Considering the specificity of the disease in the childhood, the recommendations valid for adults, modified to a certain degree, apply to the treatment of diseases in children.